Descriptive Analysis of Investment to Support Aceh's Tourism - Win Konadi; T.M. Nur; Musrizal Musrizal (Singkite Journal, 2026)
The tourism sector serves as a catalyst for development of accelerating the development process, particularly in Aceh Province, which boasts beautiful mountainous and coastal landscapes. The emergence of various tourist attractions, including new tourism villages, is supported by capital investment. This is because a reciprocal relationship exists between investment and tourism development, driving economic growth and generating employment opportunities. This study employs a descriptive qualitative analysis, examining tourism potential, visitor trends, and efforts to boost investment to support economic development, specifically within the tourism sector. By analyzing data, phenomena, and reference materials, the study describes the crucial role of the local government in developing Aceh's tourism sector; regional tourism development focuses primarily on economic aspects (such as foreign exchange and tax revenue) and social (such as job creation). Trends in tourism and investment are on the rise, driven by security guarantees for investors and strong tourist interest in visiting Aceh. Local governments in regions that implement Sharia law need to adopt creative strategies and innovations tailored to their specific contexts. Furthermore, the development of the tourism industry as a component of the economic and business landscape - requires a long-term plan.